A revisit to the role of gender in moderating the effect of emotional intelligence on leadership effectiveness: A study from Egypt - Yasmine Nabih; Hiba K. Massoud; Rami M. Ayoubi; Megan Crawford (Cogent Business & Management, 2023)
There is still no clear agreement between previous studies regarding the association between leadership effectiveness (LE) and emotional intelligence (EI), and the moderating effect of gender. In the current study, we tested the impact of (EI) on (LE) and the moderating role of gender on this relationship. We employed Hierarchical Moderated Multiple Regression analysis (MMR) for our data, which we collected from 141 questionnaires using a non-probabilistic technique from Fast-moving consumer good (FMCG) in Egypt. We found that EI is positively related to LE. The gender variable moderated both the relationship between others' emotional appraisal and LE and use of emotion and LE. Specifically, others' emotional appraisal was positively associated with LE for females, but almost unrelated for males; whereas the positive relationship between use of emotion and LE was stronger for males compared to females. The current study highlights the crucial role that human resource development and training would play in augmenting EI skills for both female and male leaders in general, and how each gender needs to better develop understanding on the other gender emotional positions. Our data was collected from a small sample of only two organizations, which hinders our ability in generalizing the findings to other organizations. While conducting future research, these aspects should be kept in mind, which can provide more valuable results. Conducting this study in Egypt contributes to the international learning experience on EI and LE in countries other than Western ones.
Keywords: 650; Emotional intelligence; gender differences; human resource development; leadership; training